International organizations : methodical recommendations for seminars and individual work (for students of the first (bachelor's) level of higher education in the specialty 291 "International Relations, Public Communications and Regional Studies" of the educational program "International Relations and Regional Studies") - Панова, Ірина Олексіївна; Panova, Iryna (Kharkiv : V.N. Karazin Kharkiv National University, 2024)
The publication contains a program of the discipline, methodical materials for seminars, organizational and methodical recommendations for individual work of higher education students and knowledge control, methodical recommendations for writing research (individual), theoretical questions for preparation for the final control. The methodical recommendations are developed for applicants of the first (bachelor's) level of higher education in the specialty 291 "International Relations, Public Communications and Regional Studies.

Видання містить програму навчальної дисципліни, методичні матеріали до семінарських занять, організаційно-методичні рекомендації до самостійної роботи здобувачів вищої освіти та проведення контролю знань, методичні рекомендації до написання науково-дослідних (індивідуальних), теоретичні питання для підготовки до підсумкового контролю. Методичні рекомендації розроблені для здобувачів першого (бакалаврського) рівня вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії».
Міжнародні організації: методичні рекомендації до семінарських занять та самостійної роботи (для здобувачів першого (бакалаврського) рівня вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії» освітньої програми «Міжнародні відносини та регіональні студії»)
Keywords: SOCIAL SCIENCES; international relations; international organizations; integration groups of the world; structure of global organizations; міжнародні відносини; міжнародні організації; інтеграційні угруповання світу; структура глобальний організацій